B2B marketing strategy : differentiate, develop and deliver lasting customer engagement - Taylor, Heidi (Marketing consultant) (2018)
Improve your B2B marketing strategy through a highly practical and unique methodology, and debunk many of the myths blighting the B2B landscape.